2010
DOI: 10.1007/s12519-010-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, triple masked, placebo-controlled clinical trial for controlling childhood obesity

Abstract: A limited period of such treatment may help weight control, and might be used to encourage those children who have been refractory to weight loss for continuing the non-pharmacological programs. Our findings should be confirmed in future studies with a longer follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…Fourteen trials were identified [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. However, 3 studies [16,20,23] were excluded for their short duration (<6 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen trials were identified [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. However, 3 studies [16,20,23] were excluded for their short duration (<6 months).…”
Section: Methodsmentioning
confidence: 99%
“…However, 3 studies [16,20,23] were excluded for their short duration (<6 months). Thus, 11 trials were selected for inclusion in this review.…”
Section: Methodsmentioning
confidence: 99%
“…36 Most trials showed BMI increases between 0.1 and 1.1 kg/m 2 in placebo groups (range = −3.2 to 0.3 kg/m 2 ). [33][34][35][36][37][38][39][40][41][42][43][44] One trial evaluated long-term metformin use in adolescents. A total of 77 obese adolescents 13 to 18 years old were randomized to metformin extended-release 1000 mg twice a day or placebo for 1 year, then followed for an additional year.…”
Section: Metforminmentioning
confidence: 99%
“…43 Appropriate dose titration does not decrease efficacy but improves tolerability and compliance. [33][34][35][36][37][38][39][40][41][42][43][44] Liver and renal function remained stable in all trials. [33][34][35][36][37][38][39][40][41][42][43][44] Yanovski et al 43 reported a statistically significant reduction in vitamin B-12 with metformin treatment.…”
Section: Metforminmentioning
confidence: 99%
“…Durchgef ü hrt wurden neben einer bundesweiten Beob achtungsstudie [10] auch interdisziplin ä r ausgerichtete Interventionsstudien, die bei Kindern (4-bis 7-j ä hrig) und bei Jugendlichen unterschiedlich angelegt sind [3,18] . International wird bei ü bergewichtigen Jugendlichen mit schlechten Interventionsergebnissen eine medikament ö se Unterst ü tzung gepr ü ft [22] . Der langfristige Erfolg derartiger Programme bedarf noch der Best ä tigung.…”
unclassified